1980
DOI: 10.1080/00103628009367111
|View full text |Cite
|
Sign up to set email alerts
|

Use of NH4 HCO3‐DTPA soil test to assess availability and toxicity of selenium to alfalfa plants

Abstract: This study was carried out to determine if ammonium bicarbonate-DTPA soil test (AB-DTPA) of Soltanpour and Schwab for simultaneous extraction of P, K, Zn, Fe, Cu and Mn can be used to determine the availability index for Se. Five Mollisols from North Dakota were treated with sodium selenate and were subjected to several wetting and drying cycles. These soils were extracted with hot water and with ammonium bicarbonate-DTPA (AB-DTPA) solution for Se analysis.Alfalfa plants were grown in these soils in a growth c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 4 publications
2
36
0
Order By: Relevance
“…3a). The exchange-phase (phosphate extractable) Se was also found to be linearly related to AB-DTP A extractable Se, which is also indicative of plant-available Se (Soltanpour and Workman, 1980). The linear increment of AB-DTP A extractable Se with increasing phosphate extractable Se indicated that adsorbed Se would be gradually transformed into plant-available Se (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…3a). The exchange-phase (phosphate extractable) Se was also found to be linearly related to AB-DTP A extractable Se, which is also indicative of plant-available Se (Soltanpour and Workman, 1980). The linear increment of AB-DTP A extractable Se with increasing phosphate extractable Se indicated that adsorbed Se would be gradually transformed into plant-available Se (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…Wan et al (1988) measured 30 to 85% reductions in shoot weight of alfalfa grown in soils containing 1.5 ppm Se. Shoot weights of alfalfa (Soltanpour and Workman 1980) and sorghum (Carlson et al 1991) were reduced approximately 25-90% and 55% by 2 and 1 ppm Se in various soils. The benchmark for Se in soil is 1 ppm.…”
Section: F1-29mentioning
confidence: 95%
“…Wan et al (1988) measured 30 to 85% reductions in shoot weight of alfalfa grown in soils containing 1.5 ppm Se. Shoot weights of alfalfa (Soltanpour and Workman 1980) and sorghum (Carlson et al 1991) were reduced approximately 25-90% and 55% by 2 and 1 ppm Se in various soils. The benchmark for Se in soil is 1 ppm.…”
Section: F1-29mentioning
confidence: 95%